Review: Pigmen Betalain sebagai Sumber Pewarna Alami dan Stabilitasnya terhadap Pengaruh Lingkungan - Ririn Betris Fatjria; Winda Nurtiana; Dinar Arum Ningtias; Andini Risma Dewi; Subianto Subianto; Nauval Alhazazie; Nanda Kurniauli P; Giberto Siburian (Universitas Muhammadiyah Semarang, 2023)
Betalain is one of the natural colorant that can be found in plants. The colors shown by betalain are red-purple and yellow-orange. Betalain stability is influenced by several factors, namely temperature, time, pH, light intensity, metal cations and oxygen. Temperature can affect the stability of betalain color pigments where betalain can last up to 60ºC. After passing this temperature limit, betalain begins to change color to become more faded, especially at temperatures of 80º-100ºC. The length of heating time also affects the betalain pigment because the pigment will be degraded. In addition, water hydrolysis also plays an important role in pigment damage in betalain by breaking the N=C bond which will cause the pigment to decompose into betalamic acid and cycloDOPA-5-O-β-glucoside. The degree of acidity (pH) can also cause betalain to degrade below pH 2 and above pH 9. At pH above 8, it will indicate the release of betalamic acid. In betalain degradation, oxygen is one of the critical factors, therefore oxygen also affects betalain pigments. Prevention of betalain pigment degradation can be done by adding ascorbic acid, removing oxygen, and adding EDTA.